ANALISIS PENERAPAN TEKNIK PENERJEMAHAN DALAM FILM PENDEK BERBAHASA ARAB DI AKUN TIKTOK @ARABIYAHTALKS - Pranindia Syafarani; Siti Aisyah (Institut Kariman Wirayudha Sumenep, 2025)
This study aims to examine the application of translation techniques in subtitles of short films in Arabic into Indonesian uploaded via the TikTok account @arabiyahtalks. Using a qualitative descriptive approach and content analysis method, data in the form of subtitle texts were analyzed based on the theoretical framework of translation techniques proposed by Molina and Albir. The results of the analysis show that modulation and literal techniques are the most dominant techniques used. Modulation techniques are used to adapt messages to the cultural context and mindset of Indonesian speakers, while literal techniques are applied when the structure of the source language allows direct translation without distortion of meaning. These findings indicate that the combination of the two techniques is able to produce translations that are not only semantically accurate, but also communicative and easy to understand by local audiences. In addition, the application of this technique is also in line with the characteristics of social media platforms such as TikTok, which emphasize clarity and conciseness in delivering audiovisual messages. This study makes a significant contribution to the development of audiovisual translation studies, especially in the context of digital content and social media in the modern era.